Case Report: Fundus findings in myelin oligodendrocyte glycoprotein-associated optic neuritis - Wilson, John R.; Cummings, Olivia W.; Elitt, Matthew S.; Van Stavern, Gregory P. (Frontiers in Ophthalmology, 2025)
Myelin oligodendrocyte glycoprotein-associated optic neuritis (MOG-ON) is a sight-threatening demyelinating disorder that can present with various ocular manifestations. Here, we describe a unique case of bilateral MOG-ON with unilateral retinal hemorrhages and Roth spots. We present the case of a 48-year-old man with acute-onset painful, severe vision loss in both eyes. Initial fundoscopic examination revealed bilateral optic nerve edema with unilateral retinal hemorrhages and Roth spots. Imaging was notable for perineural enhancement along both optic nerves. Serological testing revealed elevated MOG antibodies. The patient was treated with high-dose intravenous steroids followed by plasmapheresis, which resulted in substantial clinical improvement. We conducted a literature review of all available studies published before March 30, 2025, using PubMed, including the keywords “myelin oligodendrocyte glycoprotein-associated optic neuritis,” “myelin oligodendrocyte glycoprotein,” “optic neuritis,” “Roth spots,” and “retinal hemorrhage.” We found that this is the first reported case in a male patient—and only the third reported case overall—of retinal hemorrhages and Roth spots occurring in the context of MOG-ON. While retinal hemorrhage and Roth spots have not historically been associated with MOG-ON, recognizing the spectrum of fundoscopic findings is crucial for the early diagnosis and management of this potentially sight-threatening disease.